STREAM AS A NEW HYPERMEDIA GENRE - Aleksey V. Bolotnov (Vestnik Volgogradskogo Gosudarstvennogo Universiteta. Seriâ 2. Âzykoznanie, 2021)
The relevance of the study is due to changes in media culture evoked by new technologies that stimulate the emergence of a new hypertext genre-stylistic reality. The article examines a new media phenomenon – stream.The stream is considered as public communicative flow that takes place in real time and includes text, as well as video and audio content, organized by the streamer (the author) – information and media personality with the active involvement of other media participants of different types; it is implemented in live Internet broadcasting; it creates a variety of opportunities for any participant (from commenting, polling, to participation in action). The stream emerged from the instrumental-service approach to the development and comprehension of various relevant topics in the content presentation. The aim of the participants in this media process is self-expression and self-actualization, the incentive to be active and interact (from personal motives to socially significant ones). As a hypermedia genre it is considered on the material of media discourse “#daiDudya” with the participation of A.A. Venediktov, taking into account his linguistic and extralinguistic characteristics. The study of the stream as a new and insufficiently investigated phenomenon of modern media communication, the development of a methodology for its analysis are of interest for communicative and cognitive linguistics, media linguistics, sociology, psychology, discourse, and cultural linguistics.